Across‐Slab Propagation and Low Stress Drops of Deep Earthquakes in the Kuril Subduction Zone. Issue 16 (19th August 2022) - Turner, Alice R.; Ferreira, Ana M. G.; Berbellini, Andrea; Brantut, Nicolas; Faccenda, Manuele; Kendall, Elodie
Abstract: Deep earthquakes occur down to 700 km depth where pressure is up to two orders of magnitude greater than in the crust. Rupture characteristics and propagation mechanisms under those extreme conditions are still poorly constrained. We invert seismic waveforms for the spatial dimensions, duration and stress drop of deep‐focus earthquakes ( M w 6.7–7.7) in the Kuril subduction zone. We find stress drops of ∼1–10 MPa and rigidity‐corrected spatial dimensions and durations similar to crustal earthquakes. Radiated efficiency >1 is observed, suggesting that undershooting is prevalent in deep earthquakes, consistent with laboratory derived weakening mechanisms. Comparisons with subduction models suggest across‐slab propagation within regions with temperatures T < ∼ 1, 000°C, similar to shallow events. Hence, despite different triggering mechanisms, the same physics seems to control the rupture propagation of both shallow and deep earthquakes. Plain Language Summary: Deep earthquakes occur where subducting slabs dive into the mantle at depths of up to 700 km, where high pressures and temperatures should prevent the occurrence of earthquakes. It is not clear how deep earthquakes start or propagate under these conditions. We consider eight earthquakes in the Kuril subduction zone and estimate their properties. After correcting for the way material properties vary with depth, we find that these deep earthquakes have similar durations, spatial extents, and stress drops as shallow (<70 km) earthquakes. When we compare the earthquake spatial extents to thermal models, we find these deep earthquakes are confined to the coolest part of the slab. These findings suggest that the same physics may control the propagation of deep and shallow earthquakes. Key Points: Seismic inversion of deep earthquake properties shows low stress drops and high radiation efficiency Comparison with thermal models shows that events are mostly confined to regions with temperatures lower than 1, 000°C The same physics may control the propagation of deep and shallow earthquakes